Associations between fiction reading, trait empathy and theory of mind ability - Tabullo, Ángel Javier (2018)
Fil: Tabullo, Ángel Javier. Pontificia Universidad Católica Argentina. Facultad de Humanidades y Ciencias Económicas; Argentina